Clostridium difficile: An Important Opportunistic Pathogen in Healthcare-Associated Infections - Soohyoun Ahn; Amarat Simonne (EDIS, 2018)
Healthcare-associated infections are infections that patients can get while receiving medical treatment in a healthcare facility. One opportunistic pathogen, Clostridium difficile, has been getting more attention in recent years because of its association with antibiotic use and a high death rate among the elderly. This 7-page factsheet will provide an overview of Clostridium difficile infection (CDI) with a focus on healthcare-associated infections. Written by Soohyoun Ahn and Amarat H. Simonne and published by the UF/IFAS Department of Food Science and Human Nutrition, January 2018. http://edis.ifas.ufl.edu/fs253